"Teacher" In Uzbek Linguoculturology Conception (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In the article, to what extent is the concept of "teacher" in the culture of the Uzbek language studied, its social content and place in linguistics are considered. Of this for we have analyzed relevant works in this direction, in which this concept has different points was studied from the point of view. Its relevant characteristics as a linguistic and cultural type and Uzbek pedagogy its importance in the field of speech was determined. In addition, experimentally obtained cognitive signs are identified.